Strategic Planning for System and Information Technology Using Anita Cassidy in PT. XYZ - Ni Luh Septiana Dharmayanti; Erma Suryani (IPTEK Journal of Proceedings Series, 2019)
The management system has been one of the essential components of information technology that uses technology to support operations and management. PT XYZ has 11 departments namely Marketing, Purchasing, Human Resource, Finance, General Affair, Engineering, Warehouse, Meat Processing, Bakery, R & D, Quality Control, and Cafe divisions. The number of employees of the entire divisions is approximately ±800 people. Applications has been used in operating the main business activity at PT XYZ on daily basis. However, the applications are still based on each division which will cause the business process to be out of control and the data disintegration in each division. It can be seen as a disadvantage to the product processing as the operation takes longer; hence, it consequently requires higher production costs. Moreover, PT XYZ still uses 3 of the 7 applications that have been developed, while it's also contributed by having limited number of staff who are able to operate desktop or web-based applications. In view of the above, this study aims to develop a suitable information system strategic plan for PT XYZ. The analysis was conducted by using Anita Cassidy's Strategic Planning, wherein the planning starts from upstream to downstream of the company's business process. Anita Casidy's method consist of 4 (four) stages including visioning, analysis, direction, recommendation. The results obtained were IS strategy, IT strategy and IT management. Based on the results, it revealed that, at the visioning stage, PT. XYZ is located in quadrant I, in which quadrant 1 supports aggressive strategies. The strategy that must be determined in this condition is supporting aggressive growth policy. In the analysis, the IS trends used were device mesh, information of everything, advanced machine learning, adaptive security architecture, advanced system architecture, mesh app and service architecture. It was found 25 ITS solutions in the direction stage. For the recommendation stage, there were 4 classifications of costs: resource costs of Rp. 685,286,896, hardware costs projected at Rp. 18,400,000, license fees of Rp. 304,737,080, and miscellaneous fees to be Rp. 192,240,897